2014
DOI: 10.4049/jimmunol.1400858
|View full text |Cite
|
Sign up to set email alerts
|

Zap70 Is Essential for Long-Term Survival of Naive CD8 T Cells

Abstract: Survival of naive T cells requires engagement of T cell receptor (TCR) with self-peptide major histocompatibility antigens. The signalling pathways required to transmit this survival signal are poorly understood. Here, we ask whether the tyrosine kinase Zap70 is required to transmit survival signals in naive CD8 T cells. In the absence of Zap70 expression, thymic development is completely blocked. Using a tetracycline inducible Zap70 transgene (TetZap70), thymic development of Zap70-deficient TCR transgenic F5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…Additionally, although tTA expression did not perturb thymic T cell development (Supplementary Fig. 3e, f ), in line with observations by others 49 52 , the frequency of splenic CD4 + effector/effector memory cells was mildly reduced (Supplementary Fig. 3h ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, although tTA expression did not perturb thymic T cell development (Supplementary Fig. 3e, f ), in line with observations by others 49 52 , the frequency of splenic CD4 + effector/effector memory cells was mildly reduced (Supplementary Fig. 3h ).…”
Section: Resultssupporting
confidence: 89%
“…Along the same line, in tTA transactivator mice, we observed significant reduction in effector and effector memory T cells upon immunization and substantial impairment of the virus-specific cytotoxic T-cell response to LCMV infection. Interestingly, neither we, nor others, observed Tet-transactivator-mediated toxic effects during leukocyte development or in unchallenged mice at steady state 44 , 46 , 49 52 , 63 , with the exception of a modest reduction in the number of CD8 + cDCs. However, others have already reported that antigen presentation is not impaired in rtTA-expressing DCs upon Dox treatment 64 , therefore we anticipate that antigen presentation to T cells functions in vav-tTA mice as well.…”
Section: Discussioncontrasting
confidence: 84%
“…In Notch4 –/– mice after ozone exposure, Zap70 was up-regulated (see Supplemental Material, Table S4). Zap70 is part of the T-cell receptor and is crucial for TCR signaling and development of CD8 + cells ( Schim van der Loeff et al 2014 ). In Notch3 –/– mice, the ANOVA analysis indicated that Il33 was up-regulated after 24 hr exposure to ozone, an inducer of Th2 cytokines (see Supplemental Material, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, we identified 70 genes that could be aberrantly repressed by DNA methylation in CP‐CML CD34 − CD15 + cells and confirmed the repression of two of them in an independent cohort. Among these genes, ZAP70 encodes a kinase essential for thymopoiesis, T‐cell receptor‐dependent survival, and proliferation (Schim van der Loeff et al ., ) and is aberrantly expressed in B‐cell malignancies, such as acute lymphoblastic leukemia and chronic lymphocytic leukemia (Rassenti et al ., ). This repression could be related to the preferential commitment to the myeloid lineage in CML.…”
Section: Discussionmentioning
confidence: 99%